Sugarcane Bud set Seed Growth at Various of Planting Material Ages and Storage Periods - Muhammad Fauzan Alwani; Meiriani Sembiring; Lisa Mawarni (Jurnal Agroekoteknologi, 2018)
In order to get a good seed, the source of planting material usually uses 6 - 8 months. Storage of  sugarcane bud set aims to maintain the viability of the seeds as long as the bud set is not ready for planting. This research was conducted on the land of the Agriculture Faculty, University of Sumatera Utara, Medan in April - July 2017, using factorial randomized block design with two factors, i.e. age of planting material (6, 7, and 8 months) and storage periods (24, 48, 72 hours). The results showed that 7 months planting material gave the best plant lenght and seeds diameter. Using 7 months planting material with 72 hours storage periods gave best shoot growth percentage.